Supporting Learning? Exploring the relationship between grantee learni ng and grantmaking practice in the transparency and accountability sec tor - Ross, Jenny (INTRAC, 2015)
Learning is fundamental to work on transparency and accountability in complex environments. But how can funding practices best support learn ing?